Predicting the OTT Services Capacity based on Network Traffic Analysis - Fernandez Gualdron, Lina Maria (My University, 2015)
As part of the response to new society behavior patterns and technological advances that are occurring in our environment, OTT (Over the Top) services have appeared on the market, and they have high acceptance to be mentioned and to be analyzed. Telecom operators see how OTT solutions are replacing their traditional services. Furthermore, these services do not generate personal income rate (beyond access to the internet) that can compensate operator’s market loss. Anvia Oyj, a Telecom Finnish company, is also interested in knowing how OTT services are affecting its market and how much traffic these services generate in its network. This thesis work studied the current OTT services at Anvia Oyj; data was collected for several months and analyzed it, using a tool that was created during this thesis work and as a result, it shows the prediction about how OTT services will grow at Anvia during the next couple of months.
Keywords: Over The Top services; Quality of Experience; Predicting; PacketLogic Device; Forecasting methods; Data organization.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|